Regeneration of P5CS-transformed oil palm plantlets mediated by Agrobacterium tumefaciens - Asmini Budiani; Imam Bagus Nugroho; Hayati Minarsih; Imron Riyadi (Menara Perkebunan, 2019)
Environmental abiotic stressors particularly drought has detrimental effects upon the productivity of estate crops. Increasing the crop tolerance towards drought stress through genetic engineering is one of the strategies employed to maintain steady productivity of valuable crop, i.e. oil palm. The aim of this study was to engineer oil palm with a better tolerance towards drought by introducing P5CS (Δ1-pyrroline-5-carboxylate synthetase) gene via Agrobacterium–mediated transformation into embryogenic calli (EC). The pBI_P5CS plasmid harboring P5CS gene was transferred from Escherichia coli XL1 Blue to Agrobacterium tumefaciens AGL1 by conjugation. The positive clone of transformed Agrobacterium was then used to infect oil palm EC by the addition of 100 ppm acetosyringone. The transformed ECs were regenerated in the de Fossard (DF) media supplemented by 50 ppm kanamycin and 250 ppm cefotaxime followed by GUS assay and PCR-based screening using NPTII and P5CS1 primers. The positive EC clones were confirmed by GUS assay, which produced blue coloration on positive transformed oil palm EC. A positive result of PCR screenings was depicted by PCR products in SYBR Green staining gel agarose electrophoresis with the expected band size of ~ 0.7 kb for the NPTII gene and ~ 0.4 kb for the P5CS gene. This study has successfully selected and regenerated pBI_P5CS transformed oil palm embryogenic calli into plantlets.